INTEGRASI TEAMWORK DAN KOHESIVITAS KELOMPOK DALAM PROSES PEMBELAJARAN PESERTA DIDIK PADA PENDIDIKAN JARAK JAUH ONLINE - Suyantiningsih, Suyantiningsih (MAJALAH ILMIAH PEMBELAJARAN, 2009)
This article examines computer-supported collaborative learning. It focuses on the students in an online program where an orientation toward teamwork and the development of group cohesiveness affect overall student learning and the learning that results specifically from team interactions (team-source learning). Some researches indicate that both teamwork orientation and group cohesiveness predict student learning, with group cohesiveness mediating the relationship between teamwork orientation and student learning. Teamwork orientation and group cohesiveness appear to be equally important predictors of team source learning.